Ministry of solidarity decree no. 74 of the year 2013 amending the decree of the minister of finance no.554 of the year 2007 on the rules implementing the provisions of the social insurance law قرار وزير التضامن الاجتماعي رقم 74 لسنة 2013 بتعديل قرار وزير المالية رقم 554 لسنة 2007 بشأن القواعد المنفذة لأحكام قانون التأمين الاجتماعي الصادر بالقانون رقم 79 لسنة 1975. - Egypt; The middle east library for economic services, translator. (2025)
Ministry of solidarity decree no. 74 of the year 2013 amending the decree of the minister of finance no. 554 of the year 2007 on the rules implementing the provisions of the social insurance law promulgated by law no. 79 of the year 1975 -- schedule no. (1) the minimum and maximum limits of the insurance contribution earning وزارة التضامن الاجتماعي قرار رقم 74 لسنة 2013 بتعديل قرار وزير المالية رقم 554 لسنة 2007 بشأن القواعد المنفذة لأحكام قانون التأمين الاجتماعي الصادر بالقانون رقم 79 لسنة 1975 – جدول رقم (1) الحد الأدنى والأقصى لأجر الاشتراك التأمينى